Confronting our beliefs about poverty and discipline. (February 2019) - Fergus, Edward
Many school practitioners think of poverty as a kind of "culture, " characterized by dysfunctional behaviors that can only be corrected by imposing harsh discipline on students. Further, beliefs about poverty are often used to justify racial disparities in disciplinary referrals, achievement, and enrollment in gifted, AP, and honors courses, as well as to justify harsh punishments for "disobedience" or "disorderly conduct" or "disrespect." Edward Fergus suggests that educators learn to understand their blind spots related to race and culture and to seek out feedback on the degree to which members of the school community experience bias .